2012
DOI: 10.1080/01446193.2012.714870
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Fitting into technical organizations? Exploring the role of gender in construction and engineering management in Greece

Abstract: While there is growing interest in professional identity construction, little is known about how marginalization may influence the development of professional identity of minority professionals, such as women engineers holding middle and upper management positions in construction management. Professional identity is defined as one's professional self-concept based on attributes, beliefs, values, motives and experiences. The development of professional identity under conditions of marginalization presents an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although she identifies herself as a woman on site, a marginalised and minority identity, she places herself firmly at the centre of the operation with "her lads". She rejects 'being the outsider' and highlights her gender identity as advantageous (see Kyriakidou, 2012). This allows her to work outside the usual confines of 'managerial identity' which includes for example the implicit suppression of emotion (Hay, 2014: 511, 513).…”
Section: Discussionmentioning
confidence: 99%
“…Although she identifies herself as a woman on site, a marginalised and minority identity, she places herself firmly at the centre of the operation with "her lads". She rejects 'being the outsider' and highlights her gender identity as advantageous (see Kyriakidou, 2012). This allows her to work outside the usual confines of 'managerial identity' which includes for example the implicit suppression of emotion (Hay, 2014: 511, 513).…”
Section: Discussionmentioning
confidence: 99%
“…Data based on employment statistics of 2011 show that 27% of civil engineers and architects, 8% of technicians, 1% of craft workers, and only 5% of managers are women (Table 1). These figures are not unique to Sweden; the low percentages of women working in the construction industry and in particular, the low percentages of female managers are also prevalent in the UK (Fielden et al, 2000;Worall et al, 2010), the US (Menches and Abraham, 2007), Australia (Loosemore and Galea, 2008), Denmark (Kamp, 2005), and Greece (Kyriakidou, 2012). Clearly, the presence of women in the industry is very low and few manage to get roles as managers and higher executives in the business (Dainty et al, 2004;Watts, 2009;Kyriakidou, 2012).…”
Section: Women In the Swedish Construction Industrymentioning
confidence: 99%
“…There are examples in many countries of how women working in the construction industry are forced to either assimilate and conform to the existing masculine culture or become marginalized, discouraged, and possibly ejected from the industry (e.g. Loosemore and Galea, 2008;Powell et al, 2009;Watts, 2009;Kyriakidou, 2012). Agapiou (2002) studied men's and women's attitudes towards women in the industry and found that women's role was constantly negotiated both among men and among women.…”
Section: Introductionmentioning
confidence: 99%
“…For example, women are now pursuing higher education and entering occupations previously dominated by men, such as Science, Technology, Engineering and Mathematics (STEM: Glass et al , 2013; Cain and Leahey, 2014) industries, making such workplaces gender-atypical for women. Employee movements across gender-atypical industries are identified as a positive input to contemporary work contexts (Kyriakidou, 2012; Wallace, 2014). However, gendered organizations pose a number of problems and challenges to the minority gender.…”
Section: Gender Issues At Workmentioning
confidence: 99%
“…information technology (IT) firms) continue to garner scholarly attention, given the rise in women entering non-traditional work domains (Wallace, 2014) and the many challenges faced by them in such contexts (e.g. Denissen, 2010; Kyriakidou, 2012; Moore et al , 2008; Pilgeram, 2007; Watts, 2007; Williams et al , 2012). As Kvande (1999) finds, women employed in these contexts cross the border of gender-atypical labor to enter highly technical professions and in doing so become the numerical and normative minority in organizations where men have the greater ruling power.…”
Section: Introductionmentioning
confidence: 99%